Scalia’s Constitution
XII, 151 p.
Keywords: This book explores the application of Scalia’s textualism and originalism to education law and reflects upon Scalia’s teachings and his pedagogy. Education law may seem to be an odd vehicle for considering Scalia’s constitutional approach, but thinking about schools requires attention to political fundamentals—freedom of speech, free exercise of religion, equality of opportunity, federalism, and the proper role of the expert. Legal scholars, philosophers, and political scientists provide both critiques and apologies for Scalia’s approach.